ARTISTIC INTERPRETATION OF THE FOLKLORIC CHRONOTOPE IN ENGLISH AND AMERICAN LITERATURE IN THE CONTEXT OF NATIONAL-CULTURAL MENTALITY - Niyazova Mokhichekhra Khayatovna; Qodirova Zebiniso Sobir qizi (Western European Studies, 2025)
This article explores the artistic interpretation of the folkloric chronotope in English and American literature within the framework of national-cultural mentality. Drawing on the theoretical perspectives of M. Bakhtin, Y. Lotman, G. Bachelard, and V. Propp, the study analyzes spatial and temporal representations in key folklore texts. English and American folkloric chronotopes are examined through specific literary examples to reveal how they reflect cultural values, social norms, and collective memory. Additional folktales are analyzed to deepen understanding of chronotopic structures and their relation to national identity and cultural pedagogy
Keywords: folkloric chronotope; English literature; American literature